Use of Ultrasonic Cleaning Technology in the Whole Process of Fruit and Vegetable Processing - Wenhao Zhou; Frederick Sarpong; Cunshan Zhou (Foods, 2022)
In an era of rapid technological development, ultrasound technology is being used in a wide range of industries. The use of ultrasound technology in fruit and vegetable processing to improve production efficiency and product quality has been an important research topic. The cleaning of whole fresh fruits and vegetables is an important part of fruit and vegetable processing. This paper discusses the development process of components of the ultrasonic equipment, the application of ultrasonic technology in fruit and vegetable cleaning, and the research advances in ultrasonic cleaning technology. Moreover, the feasibility of ultrasonication of fruits and vegetables for cleaning from the perspectives of microbial inactivation, commodity storage, and sensory analysis were discussed. Finally, the paper identified the inevitable disadvantages of cavitation noise, erosion, and tissue damage in fruit and vegetable processing and points out the future directions of ultrasonic fruit and vegetable cleaning technology.